NARRATIVE CONSTRUCTION OF FOOD SOVEREIGNTY IN INSTAGRAM CAPTIONS BY @lakoat.kujawas (Proceedings of the World Conference on Media and Mass Communication, 2025)
The global food crisis has become a significant issue worldwide. As a multicultural country, Indonesia faces this challenge by increasing rice production as the ultimate way to achieve food security. However, many food activists and communities argue that food sovereignty offers a more appropriate solution. This research examines how Lakoat Kujawas, a food community from Mollo, East Nusa Tenggara, promotes food sovereignty through messages on their Instagram account, @lakoat.kujawas. This study adopts an interpretive paradigm and employs a narrative analysis approach. Preliminary findings reveal that Lakoat Kujawas actively introduces local food to raise public awareness about food sovereignty. They use Bahasa Indonesia combined with local languages to enhance their message and redefine local food as an ongoing effort to respond to environmental challenges. To gain broader visibility, they utilize hashtags such as #SehariTanpaNasi (#ADayWithoutRice) in some of their Instagram posts, collaborate with communities from different fields such as Kata Kerja and inform their participation in international events such as Makassar International Writers Festival (MIWF). This demonstrates their potential as a valuable contributor to addressing global food issues.
Keywords: food sovereignty; Lakoat Kujawas; narrative analysis; local food